Effect of Bacillus cereus exocellular factors on human intestinal epithelial cells - Minnaard, Jessica (2001)
To gain insight on the biological effects of the exocellular factors produced by Bacillus cereus, culture filtrate supernatants of different strains were coincubated with differentiated Caco-2 cells. Exocellular factors were able to detach enterocyte-like cells from the substratum after 1 h of incubation. In addition, microvilli effacing and dramatic changes on the cellular surface of enterocytes were found after incubation periods as short as 20 min. Since cell detachment was not inhibited by fetal calf serum, thiol activated cholesterol-binding cytolysin, cereolysin O, does not seem to be involved. Also, translocation of phosphatidylserine from the inner to the outer leaflets of the plasma membrane was demonstrated by using fluorescein isothiocyanate (FITC)-Annexin V. In contrast to the high capability of detaching Caco-2 cells shown by all the strains under study, the mitochondrial dehydrogenase activity was lowered by culture filtrate supernatants in a strain-dependent manner. For strain M2, the decrease in dehydrogenase activity was already evident after 30 min of incubation. Production of biologically active factors depends on the growth phase, and maximal activity was found in late exponential-early stationary phases. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) of concentrated exocellular factors showed a very complex scenery supporting the multifactorial character of the biological activity of B. cereus.